THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE - Marnoto Marnoto; Sopi Sopi (Adisam Publisher, 2025)
This research aims to examine the influence of transformational leadership on employee performance through a comprehensive literature review. Transformational leadership, which is characterized by four main components, namely idealistic influence, inspirational motivation, intellectual stimulation, and individual consideration, has been proven to have a significant impact on various aspects of employee performance. This study collects and analyzes results from various empirical studies to explore how each component of transformational leadership contributes to increased productivity, creativity, and employee engagement. The main findings from the literature review show that transformational leadership has a positive and significant impact on employee performance. The influence of idealistic and inspirational motivation encourages employees to achieve organizational goals with high enthusiasm and commitment. Intellectual stimulation increases the capacity for innovation and engagement in problem solving, while individualized consideration strengthens employee loyalty and professional development. The implications of these findings suggest that organizational leaders adopt a transformational leadership style if they want to improve the performance of their teams. Additionally, organizations are advised to implement leadership training that focuses on developing transformational capabilities to achieve long-term effectiveness. This research also opens up opportunities for further studies regarding the application of transformational leadership in various different cultural and industrial contexts.